How to Apply Ecoprint Learning Media in Yogyakarta Schools? - Pranestya Diva Poetmayona; I Ketut Sunarya (Smart Society, 2026)
Ecoprint has become a popular creative industry trend in Yogyakarta. However, this popularity has not been offset by the availability of systematic learning media in schools, making it difficult for students to absorb local materials effectively due to the lack of interactive visual guidance. This study aims to analyze the effectiveness of the application of ecoprint learning media. The method used was quantitative descriptive with a closed questionnaire. The respondents consisted of 23 art teachers and 157 junior and senior high school students in Yogyakarta, selected through purposive sampling based on the criteria of active involvement in art learning. The results of the study showed that teachers and students were very enthusiastic about the use of ecoprint media with a percentage above 71%. Therefore, the development of varied and interactive learning media is needed to increase focus and deepen students' understanding of adaptive local wisdom art learning in schools.